2018
DOI: 10.1093/toxsci/kfy291
|View full text |Cite
|
Sign up to set email alerts
|

Detection and Prioritization of Developmentally Neurotoxic and/or Neurotoxic Compounds Using Zebrafish

Abstract: The standard methods for toxicity testing using rodent models cannot keep pace with the increasing number of chemicals in our environment due to time and resource limitations. Hence, there is an unmet need for fast, sensitive, and costeffective alternate models to reliably predict toxicity. As part of Tox21 Phase III's effort, a 90-compound library was created and made available to researchers to screen for neurotoxicants using novel technology and models. The chemical library was evaluated in zebrafish in a d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
22
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 33 publications
(23 citation statements)
references
References 48 publications
(57 reference statements)
1
22
0
Order By: Relevance
“…acenaphthenequinone, hydroquinone, and tributyltin oxide. In the developmental toxicity assay here, NOEL values for these compounds were similar to those previously reported (Knecht et al 2013;Truong et al 2014;Quevedo et al 2019;USEPA 2019). Although changes in ROS production in the zebrafish RBA were not observed here, hydroquinone has been shown to modulate ROS production in cell-based assays (Lee et al 2007).…”
Section: Compounds With Developmental But No Observable Immunotoxicitysupporting
confidence: 88%
“…acenaphthenequinone, hydroquinone, and tributyltin oxide. In the developmental toxicity assay here, NOEL values for these compounds were similar to those previously reported (Knecht et al 2013;Truong et al 2014;Quevedo et al 2019;USEPA 2019). Although changes in ROS production in the zebrafish RBA were not observed here, hydroquinone has been shown to modulate ROS production in cell-based assays (Lee et al 2007).…”
Section: Compounds With Developmental But No Observable Immunotoxicitysupporting
confidence: 88%
“…It has been previously shown that changes in larval behaviour can be used as an indicator of neurotoxicity [ 7 , 8 , 25 ]. These studies tested larval behaviour following similar exposure paradigms to the aforementioned ZET assays.…”
Section: Discussionmentioning
confidence: 99%
“…The zebrafish ( Danio rerio ) is an established alternative model for toxicity testing that can provide a medium-throughput, cost-effective model that can also provide more information than can be obtained from cell line testing alone [ 1 ]. Additionally, it has been established that until zebrafish reach the protected animal stage at 5 days post fertilization (dpf) they can be considered an alternative model to animal testing [ 2 , 3 , 4 , 5 , 6 , 7 , 8 , 9 ]. The zebrafish larval model of toxicity testing is now included as an Organization for Economic Cooperation and Development (OECD) Fish Embryo Toxicity (FET) model [ 10 , 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…Wild-type zebrafish ( Danio rerio ; strain AB) were bred and housed at Biobide (San Sebastián, Spain) in accordance with standard procedures (Zebrafish Information Network) as described previously [ 3 , 51 ]. In brief, the fish were maintained in a 300-L aquarium with a maximum of 1000 fish per tank.…”
Section: Methodsmentioning
confidence: 99%